Türk hukukunda idari yargı kararları ışğında kamu hizmetinin yürütülmesinden kaynaklanan kamu gücünün kusursuz sorumluluğunun esasları - Baş Bereket, Zuhal (My University, 2002)
Modern toplumda bireyin öneminin artması, kamu hizmetinin tanımında bireye yer verilmesi ve bireyin ihtiyaçlarını karşılamaya yönelmesi klasik nitelendirmelerin değişimine neden olmuştur. Hukuk devletinin sorumlu devlet anlayışını öngörmesi; sosyal devletin tazmin eden devlet kuramını yerleştirmesi önemli değişimlerdir. Bütün bu değişimler kamu gücünün sorumluluğu kavramının ortaya çıkışın ve gelişmesini hazırlayan etmenlerdir. Kamu gücünün sorumluluğu konusunda idare hukukunda, idarenin hizmet kusuru ilkesi uyarınca kusurlu işlettiği hizmetlerden dolayı tazmin sorumluluğunun varlığı kabul edilmiştir. Kamu gücün elinde tutan idarelerin yürüttükleri kamu hizmetlerini kötü işletmeleri, hiç işletmemeleri ya da geç işletmeleri hizmet kusur ilkesine göre idareyi sorumluluğa götürür. Zaman içinde teknolojide meydana gelen değişimler, idarenin kusurunu tespitteki güçlükler gibi nedenler kamu gücünün kusur olmasa bile sorumlu olması sonucunu doğuran kusursuz sorumluluk ilkesinin ortaya çıkmasını hazırlamıştır. Kusursuz sorumluluk kuramı; kamu hizmetinin içindeki risk nedeniyle “tehlikelilik” , kamu hizmetinin yürütülmesinden idarenin elde ettiği fayda ile, bireyin bu hizmet nedeni ile uğradığı zararın üzerinde bırakılmayıp topluma paylaştırılması düşüncesinin ürünü olan “kamu yükümlülükleri karşısında eşitlik” ilkesi gibi ilkelerle genişlemiştir. Nedensellik bağı olan bu sorumluluk halinin zaman içinde ihtiyaçlara cevap vermemesi, bireyin toplumun sırf bir ferdi olması nedeni ile uğradığı zararların tazminini amaçlayan “sosyal risk” ilkesini doğurmuştur. Şüphesiz bireyin uğradığı zararların idarece tazmin edilebilmesi için, idarenin zarar verici bir faaliyetinin varlığı, zararın olağan üstü, anormal, özel ve spesifik olması gerekir. Ayrıca idarece bu zararların tazmini için zararla kamu hizmeti arasında nedensellik bağını ortadan kaldıracak mücbir sebep, umulmayan hal,mağdurun kusuru, üçüncü kişinin kusuru, kamu görevlisinin şahsi kurusu gibi nedenlerin olmaması zorunludur.

The increase of the importance of the individual in the modern society and individual being included within the definition of public service, along with the individual becoming more inclined to satisfy his or her own needs have resulted in a change in the classical characterizations. Governments with predominating understanding of law putting forward the vision of a responsible government; Social governments maintaining the theory of compensating government are very significant changes. All these changes are the factors that make way for the arise and development of responsibility of the public power. About the responsibility of the public power, contained within the administrative law, it is accepted that there exists a commitment for compensation on the services being operated faultily, according to the principle of service fault of the administration. According to this principle of service fault, administrating bodies that hold the public power being faulty or delayed on their services or entirely failing to provide these said services leads the administrating body to be liable for its actions. Technological achievements throughout the time, and reasons such as the determination of the faulty action by the administrating body being hard, have put the principle of faultless responsibility that creates the consequence of public power being liable even if there is no fault, into existence. Faultless responsibility principle, have been extended by including principles like “equality with respect to public obligations” which is a product of the idea that dictates the distribution of the gain of the administrative body by carrying out the public services, the “danger” arising from the risk contained within the public service on the whole population as well as doing the same for the possible damage caused on the individual through this service, instead of letting the individual to take the whole damage. This state of responsibility that has causality relation to become inept at meeting the requirements in time has resulted in the birth of a principle, “social risk principle” that aims to compensate for the damages or losses visited upon the individual just because the individual is a member of the society. Needless to say, for the damages or losses to be compensated by the administrative body, it is required that there is indeed a damaging action by the administrative body, the damage to be extraordinary, abnormal, special and specific. Moreover, it is obligatory that there exists no aspect to the case such as force majeur, unexpected condition, fault of the subject individual, personal fault of the public official, that can remove the causality relation between the damage and the public service, for the compensation of the damage to be possible.
Keywords: Hukuk-kamu Hukuku; Kamu Hukuku Türkiye